2019
DOI: 10.1016/j.waojou.2019.100064
|View full text |Cite
|
Sign up to set email alerts
|

Mometasone furoate is not superior to saline for chronic rhinitis in the elderly

Abstract: IntroductionPrevalence of diseases associated with ageing is rising; among these are the rhinologic problems. Chronic rhinitis appears as one of the most common worrisome nasal disorders in this age group. At the same time, the allergic form diminishes because of the immunosenescence.ObjectiveThis study aimed to evaluate the effect of a corticosteroid nasal spray (mometasone furoate) over nasal patency and the severity of rhinitis and its impacts on quality of life as compared with the saline nasal spray.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The placebo had significant improvements for the VAS, the RQLQ score, and the TNR when compared to baseline due to the therapeutic effect of normal saline in relieving AR symptoms [47]. Meta-analyses showed that saline irrigation served as a safe adjunct to AR treatment among children and adults [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The placebo had significant improvements for the VAS, the RQLQ score, and the TNR when compared to baseline due to the therapeutic effect of normal saline in relieving AR symptoms [47]. Meta-analyses showed that saline irrigation served as a safe adjunct to AR treatment among children and adults [48,49].…”
Section: Discussionmentioning
confidence: 99%